ARABIC SPEAKING SKILLS OF ARABIC LANGUAGE EDUCATION STUDY PROGRAM STUDENTS IN JAMBI PROVINCE - Budi Sanjaya; Ali Murtadlo (Lughawiyah: Journal of Arabic Education and Linguistics, 2026)
Arabic speaking skills are one of the important components in language mastery, especially for students of the Arabic Language Education Study Program. This study aims to describe and analyze students' ability to speak Arabic. The study used a quantitative approach using an evaluation method. Data were collected using a speaking skills test on 117 third-semester Arabic language education program students who had passed the muhadatsah li al Mutawassitin or Muhadatsah II course at State Universities in Jambi Province, including the State Islamic University of Sultan Thaha Saifuddin (UIN STS) Jambi, the State Islamic Institute of Kerinci (IAIN Kerinci) and the University of Jambi (UNJA). The data were analyzed descriptively using the average, standard deviation, frequency and percentage. The results showed that Arabic speaking skills in Jambi were categorized as good. The aspects of fluency, comprehension, vocabulary, grammar, pronunciation, intonation and stress were categorized as quite good. There was no significant difference in students' Arabic speaking skills between the three state universities in Jambi Province.